Combined Effect of Virechana and Jalaukavacharana in Vicharchika (AYUSHDHARA, 2021)
Now a day’s stress is a very common factor to every human being (even children). Now people are not only conscious about health but also very much serious about their beauty. So even a small pimple they cannot tolerate anymore. But as we know skin disorders are psychosomatic as explain in modern as well as in Ayurveda. So clinician encounter with so much cases of skin disorder in day to day practice, all type of skin diseases are explained under Kustha in Ayurveda. There are 2 types of Kustha like Maha kustha and Kshudra kustha, Vicharchika is explained under Kshudra Kustha, which is Kapha, Pitta, Rakta pradhana. It can be compared with eczema in modern times which is having prevalence rate of 26.95%. In children of north India prevalence is only 0.01% where in South India prevalence is 2.8%. In conventional system of medicine other than corticosteroids there is no particular treatment for Vicharchika but in Ayurveda it can be managed with various line of management like Shaman Aushadis, Shodhana like Virechana and Raktamokshana have more effective and useful. The present study is designed to evaluate the effect of Shodhan (Virechana & Jalaukavacharana) along with Shamana aushadis.